ANOTHER PROOF OF WIENER’S SHORT SECRET EXPONENT
Wiener’s short secret exponent attack is a well-known crypt-analytical result upon the RSA cryptosystem using a Diophantine’s method called continued fractions. We recall that Wiener’s attack works efficiently on RSA with the condition that the secret exponent <a href="https://www.codecogs.com/eqnedit.php?latex=d<&space;13N^14 " target="_blank"><img title="d< 13N^14 " src="https://latex.codecogs.com/gif.latex?d<&space;13N^14 " alt=""> . Later, the upper bound was improved satisfying <a href="https://www.codecogs.com/eqnedit.php?latex=d<62 6N^14 " target="_blank"><img title="d<62 6N^14 " src="https://latex.codecogs.com/gif.latex?d<62 6N^14 " alt=""> . In this work, we present another proof to Wiener’s short secret exponent satisfying <a href="https://www.codecogs.com/eqnedit.php?latex=d<12&space;N^14 " target="_blank"><img title="d<12 N^14 " src="https://latex.codecogs.com/gif.latex?d<12&space;N^14 " alt="">. We remark that our result is slightly better than the previously mentioned attacks. , number=Sp 1, journal=Malaysian Journal of Science, author=Asbullah, Muhammad Asyraf and Kamel Ariffin, Muhammad Rezal, year=2019, month=Feb., pages=67–73